2017
DOI: 10.31227/osf.io/t796p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Corporate Governance and Corporate Social Responsibility on Financial Performancewith Efficiency as Mediating Variable

Abstract: The purpose of this research was to investigate and analyze the direct effect of corporategovernance and corporate social responsibility on financial performance and their indirect effect throughefficiency. This research used quantitative approach with samples of manufacturing firms which were selectedusing purposive sampling that listed in Indonesia Stock Exchange. There were 297 observations years-firms(2009-2012). The results of this research showed that corporate governance didn’t have effect on financialp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
0
7
0
1
Order By: Relevance
“…While corporate governance theories were unique, their practical results were not conclusive. Numerous studies, particularly in developing countries, still show that there is no relationship between corporate governance practices and firm performance; for example, Aboagye and Otieku (2010) in Ghana, Jamali et al (2015) in Indonesia, Shahwan (2015) in Egypt and, finally, Arora and Sharma (2016) in India. In this context, both Shahwan (2015) and Bhatt and Bhatt (2017) ascribe this unclear association between corporate governance practices and firm performance to the voluntary, rather than mandatory, adoption of the corporate governance code.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…While corporate governance theories were unique, their practical results were not conclusive. Numerous studies, particularly in developing countries, still show that there is no relationship between corporate governance practices and firm performance; for example, Aboagye and Otieku (2010) in Ghana, Jamali et al (2015) in Indonesia, Shahwan (2015) in Egypt and, finally, Arora and Sharma (2016) in India. In this context, both Shahwan (2015) and Bhatt and Bhatt (2017) ascribe this unclear association between corporate governance practices and firm performance to the voluntary, rather than mandatory, adoption of the corporate governance code.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Others related CSR activities to profitability (Dabbas and Al-rawashdeh, 2012;Persic and Markic, 2013;Khan and Majid, 2013;Malik and Nadeem, 2014;Jamali et al, 2015;Jamali et al, 2015;Kaur, 2015;Emezi, 2015). Moreover, some related CSR to shareholders' wealth (Mujahid and Abdullah, 2014;Dzhavdatovna et al, 2015), market share and performance (Khan and Majid, 2013;Al-Ani and Jamil, 2015), operating performance (Razafindrambinina and Sabran, 2014), credit, company's success and position (Mousavi, 2013), employee satisfaction and increased productivity and profitability (Togun and Nasieku, 2015) and to all financial performance measurements, such as return on assets, return on equity and return on sales (Bidhari et al, 2013) and total assets (Abdulrahman, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research (e.g., Mahrani & Soewarno, 2018;Rao, 2018;Shaji & Shajahan, 2020;Khan et al, 2021;He, 2021;Al-Faryan, 2021) discovered that CG had a considerable beneficial influence on financial performance, while others discovered that it had a negative impact (e.g., Latif et al, 2014;Zabri et al, 2016;Al-ahdal et al, 2020;He, 2021). Additionally, research has shown that CG has little impact on a company's performance financially, either directly or indirectly (Buallay et al, 2017;Jamali et al 2017;Al-ahdal et al, 2020). While the definitions of the dimensions of CG implementations were not agreed upon in the earlier studies.…”
Section: Literature Review and Hypothesis Corporate Governance (Cg)mentioning
confidence: 99%